Analisis Kemampuan Berpikir Kritis dalam Menafsirkan Soal Cerita Matematika pada Siswa Kelas 5 SDN Sukaasih 1 Kabupaten Tangerang - Khoirunnisa, Tasya Nurfadila; Unaenah, Een; Rini, Candra Puspita (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Mathematics is a subject that requires high critical thinking skills to be able to understand problems. Especially for working on questions in story form. Therefore, this research aims to analyze the critical thinking abilities of class 5D students in interpreting mathematics story problems on block volume material. This research uses qualitative research with a descriptive approach. The subjects in this research were 15 students in class 5D at SDN Sukaasih 1. Data collection techniques use tests, interviews and documentation. from test results, interviews, and documentation. This research data analysis uses data reduction, data presentation, and drawing conclusions. The research results showed that out of a total of 15 students, 2 students had high critical thinking abilities, 2 students had moderate critical thinking abilities, and 11 students had low critical thinking abilities. Based on the research results, the researcher concluded that the critical thinking abilities of class 5D students at SDN Sukaasih 1 were in the low category. Therefore, the critical thinking skills of class 5D students at SDN Sukaasih 1 still need further training so that they can be improved.